Myocardial delayed enhancement in pulmonary hypertension: pulmonary hemodynamics, right ventricular function, and remodeling - Shehata, Monda; Loßnitzer, Dirk; Skrok, Jan; Boyce, Danielle; Lechtzin, Noah; Mathai, Stephen C.; Girgis, Reda E.; Osman, Nael; Lima, Joao A. C.; Bluemke, David A.; Hassoun, Paul M.; Vogel-Claussen, Jens (American journal of roentgenology, 2011)
OBJECTIVE. The purpose of this study was to assess predictors of MRI-identified septal delayed enhancement mass at the right ventricular (RV) insertion sites in relation to RV remodeling, altered regional mechanics, and pulmonary hemodynamics in patients with suspected pulmonary hypertension (PH). - - SUBJECTS AND METHODS. Thirty-eight patients with suspected PH were evaluated with right heart catheterization and cardiac MRI. Ten age- and sex-matched healthy volunteers acted as controls for MRI comparison. Septal delayed enhancement mass was quantified at the RV insertions. Systolic septal eccentricity index, global RV function, and remodeling indexes were quantified with cine images. Peak systolic circumferential and longitudinal strain at the sites corresponding to delayed enhancement were measured with conventional tagging and fast strain-encoded MRI acquisition, respectively. - - RESULTS. PH was diagnosed in 32 patients. Delayed enhancement was found in 31 of 32 patients with PH and in one of six patients in whom PH was suspected but proved absent (p = 0.001). No delayed enhancement was found in controls. Delayed enhancement mass correlated with pulmonary hemodynamics, reduced RV function, increased RV remodeling indexes, and reduced eccentricity index. Multiple linear regression analysis showed RV mass index was an independent predictor of total delayed enhancement mass (p = 0.017). Regional analysis showed delayed enhancement mass was associated with reduced longitudinal strain at the basal anterior septal insertion (r = 0.6, p < 0.01). Regression analysis showed that basal longitudinal strain remained an independent predictor of delayed enhancement mass at the basal anterior septal insertion (p = 0.02). - - CONCLUSION. In PH, total delayed enhancement burden at the RV septal insertions is predicted by RV remodeling in response to increased afterload. Local fibrosis mass at the anterior septal insertion is associated with reduced regional longitudinal contractility at the base.